2019
DOI: 10.1080/14397595.2018.1553489
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tofacitinib in Japanese patients with rheumatoid arthritis by background methotrexate dose: A post hoc analysis of clinical trial data

Abstract: Objectives: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). We investigated concomitant methotrexate (MTX) dose on tofacitinib efficacy/safety in Japanese RA patients. Methods: This post hoc analysis pooled data from a 3-month phase 2 study (NCT00603512) and a 24-month phase 3 study (NCT00847613). Patients (N¼ 254) received tofacitinib (low-dose (1 or 3 mg), 5 mg, 10 mg) twice daily (BID) or placebo, with low-dose (>0 to 8 mg/week) or high-dose (>8 mg/week) MTX. Efficacy (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…This may be the result of the relatively higher proportion of Asian patients in the peficitinib clinical trials than in tofacitinib and baricitinib trials; due to the interaction between Asian ethnicity and the responses listed in the previous paragraph, the relative efficacy of peficitinib versus the other two JAK inhibitors was reduced once analyses were adjusted for the percentage of Asian patients. These results are consistent with data from previous trials, which showed that tofacitinib had greater efficacy in Asian patients than in [41,42]. We have also observed that peficitinib performed better in clinical trials in patients in Asian countries [9,10] compared with those in a global trial reported by Kivitz et al [43], despite the fact that patients in all three trials had had an inadequate response to MTX, and also predominantly moderate-tosevere RA according to baseline DAS28 or other validated composite measures of disease activity [9,10,43].…”
Section: Discussionsupporting
confidence: 92%
“…This may be the result of the relatively higher proportion of Asian patients in the peficitinib clinical trials than in tofacitinib and baricitinib trials; due to the interaction between Asian ethnicity and the responses listed in the previous paragraph, the relative efficacy of peficitinib versus the other two JAK inhibitors was reduced once analyses were adjusted for the percentage of Asian patients. These results are consistent with data from previous trials, which showed that tofacitinib had greater efficacy in Asian patients than in [41,42]. We have also observed that peficitinib performed better in clinical trials in patients in Asian countries [9,10] compared with those in a global trial reported by Kivitz et al [43], despite the fact that patients in all three trials had had an inadequate response to MTX, and also predominantly moderate-tosevere RA according to baseline DAS28 or other validated composite measures of disease activity [9,10,43].…”
Section: Discussionsupporting
confidence: 92%
“…Post hoc analyses have suggested that concomitant MTX has minimal impact on efficacy, compared with bDMARD monotherapy (including adalimumab, etanercept, and infliximab) [22,23]. Assumptions regarding the impact of varying MTX dose on the efficacy and safety of bDMARDs or tsDMARDs in PsA may be drawn from post hoc analyses of RA studies [24][25][26]. For example, in a post hoc analysis of a phase III trial of tofacitinib in patients with RA, varying the MTX dose used in combination with tofacitinib had minimal effect on key endpoints, such as ACR and the Health Assessment Questionnaire-Disability Index (HAQ-DI) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) in different countries have evaluated the efficacy of tofacitinib, baricitinib, peficitinib, upadacitinib, filgotinib and decernotinib as monotherapy in patients with RA by comparing them with placebo [3,[6][7][8][9][10], in which different JAK inhibitors showed better efficacy compared to placebo, but because the data from head-tohead studies comparing various JAK inhibitors at different doses are sparse, it is necessary to compare the efficacy of different JAK inhibitors at different doses in combination with evidence from RCTs of different treatments. Thie present study used a Bayesian reticulation meta-analysis to examine the relative efficacy and safety of various JAK inhibitors in RA patients.…”
Section: Introductionmentioning
confidence: 99%